Predictors of high on-clopidogrel platelet reactivity in patients with acute coronary syndrome. (17th February 2016) - Lee, Sarolta; Hizoh, Istvan; Kovacs, Andrea; Horvath, Zsofia; Kiss, Nora; Toth-Zsamboki, Emese; Kiss, Robert Gabor
Abstract: High on-clopidogrel platelet reactivity (HPR) is a predictor of ischemic events after percutaneous coronary intervention. We conducted a prospective cohort study to identify variables related to HPR in acute coronary syndrome patients who are at high thrombotic risk. We enrolled 463 patients undergoing urgent coronary angiography. Platelet reactivity was measured 12–36 hours after 600 mg clopidogrel loading with multiple electrode aggregometry (Multiplate® analyzer, Roche, Basel, Switzerland, 6.4 µM ADP). HPR was defined by the consensus cut-off area under the curve >46 U. The rate of HPR was 16.0%. We analyzed simple clinical and laboratory parameters with backward multivariate logistic regression and identified the following predictors of HPR: platelet count (per G/L, OR: 1.0073, 95% CI: 1.0035–1.0112, p  = 0.0002), CRP level (per mg/L, OR: 1.0077, 95% CI: 1.0016–1.01372, p  = 0.01), and active smoking (OR: 0.51, 95% CI: 0.29–0.89, p  = 0.02). We developed and internally validated a risk prediction model demonstrating moderate discriminative capacity (area-under-the-receiver operating characteristic curve = 0.67). In conclusion, we found a relatively low rate of high on-clopidogrel platelet reactivity (16.0%) even in an acute patient cohort. HPR measured by Multiplate was associated with high platelet count and CRP level on admission and was inversely related to active smoking. The model with rapidly available simple parameters might help to identify individuals at risk for HPR in the acute setting.